THE USE OF INSTAGRAM AS A MARKETING COMMUNICATION STRATEGY AT PT. BENLARIS SAHABAT DEWATA - Indah Pratiwi, Nuning; Satrianingsih, Desak Putu Chandra; Satria, Wahyu Indra (Qawwam : The Leader's Writing, 2025)
With the development of technology and the increasing popularity of social media, Instagram has become the main platform for companies to build brand awareness, interact directly with the audience, and promote products. In this study, the researcher aims to understand the use of Instagram as a marketing communication strategy at PT. Benlaris Sahabat Dewata. This study uses a qualitative approach to explore the utilization of Instagram features such as Stories, Reels, and Instagram Ads in increasing engagement and expanding audience reach. The research results show that Instagram is effective in building personal relationships with customers and increasing brand visibility, although PT. Benlaris Sahabat Dewata faces challenges related to content consistency and message adaptation for a diverse audience. Through the implementation of the Integrated Marketing Communication (IMC) approach, PT. Benlaris Sahabat Dewata can optimize their marketing communication strategy, ensuring that the messages conveyed remain relevant, engaging, and effective in achieving business goals